Theory of Elementary Contribution to Profit Transformation in the Concept of the Company and a Platform for the Realization of Islamic Banking - Sayed Amrollah Hoseini; Mohammad Zarei Mahmoudabadi (تحقیقات مالی اسلامی (پیوسته))
In the opinion of famous Imami jurists, company is synonymous with admixturing. It means combining rights and properties in a way that cannot be.distinguished. which may be achieved due to optional means such as contract, menstruation, mixing or coercive means such as inheritance, mixing and the like.In this case, the matter is limited to those cases in which the combination is possible.Therefore, things like the company's debt, interests, actions and credits, which are ironically common in today's economy and banking, are out of the scope of the company. But can the agreement of both parties be the cause of diffusion and participation? And is it possible to realize the company without distribution? Or according to the traditional theory of diffusion in the realization of the company? The present research has tried to answer this question And by studying the sayings of the jurists by the method of induction and data analysis, he has come to the conclusion that The concept of participation in the thought of Imami jurists has evolved and evolved And according to the latest belief, diffusion is not a condition for the realization of the company Rather, initial participation in profit is sufficient without mixing of properties. By accepting this concept of the company, the challenges facing the traditional theory of the company have been resolved A new platform is provided for the realization of Islamic banking.